Skeptic in Salem: An Episode of Murder (A Dubious Witch Cozy Mystery-Book 1) - Fiona, Grace (Lukeman Literary, 2020)
"Very entertaining. Highly recommended for the permanent library of any reader who appreciates a well-written mystery with twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews (regarding Murder in the Manor) SKEPTIC IN SALEM: AN EPISODE OF MURDER is the debut novel in a charming new cozy mystery series by bestselling author Fiona Grace, author of Murder in the Manor, a #1 Bestseller with over 100 five-star reviews (and a free download)! When Mia Bold, 30, learns that the pharmaceutical company she works for only cares about money, she quits on the spot, walking away from a high-powered career. Worse, her long-time boyfriend, instead of proposing as she expected, decides to break up with her. Mia's true passion lies in her own podcast, devoted to debunking the occult and shining light on the truth. The daughter of a con-man father, Mia feels a moral responsibility to the truth, and to spare others from being conned. When Mia, at a crossroads, receives an invitation from a famous supernatural podcast inviting her to move to Salem and join their podcast as the skeptic-in-residence, Mia sees a chance to start her life over again and to pursue her life's mission. But things in Salem do not go as planned. When an unexpected death happens-in the midst of Mia trying to debunk a haunted inn-she realizes she may be in over her head. With her own future now at stake, can she really prove that witches and ghosts do not exist? A mesmerizing page-turner, packed with intrigue, mystery, romance, pets, food-and most of all, the supernatural-SKEPTIC IN SALEM is a cozy with a twist, one you will cherish as it has you fall in love with its main character and as it keeps you glued (and laughing) throughout the night. "The book had heart and the entire story worked together seamlessly that didn't sacrifice either intrigue or personality. I loved the characters - so many great characters! I can't wait to read whatever Fiona Grace writes next!" --Amazon reviewer (regarding Murder in the Manor) "Wow, this book takes off & never stops! I couldn't put it down! Highly recommended for those who love a great mystery with twists, turns, romance, and a long lost family member! I am reading the next book right now!" --Amazon reviewer (regarding Murder in the Manor) "This book is rather fast paced. It has the right blend of characters, place, and emotions. It was hard to put down and I hope to read the next book in the series."
Keywords: Krimi, detektivky